2015
DOI: 10.1007/s11581-015-1487-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palladium oxide electrode on potentiometric sensor response to carbon monoxide

Abstract: This study aims to explore the potential merits of palladium oxide sensing electrode. PdO is applied on a solidstate potentiometric sensor on an yttria-stabilized zirconia (YSZ) electrolyte as sensing electrode for the first time. The physical properties, morphology, chemical properties, and sensing performance of synthetic PdO electrode are characterized. An attractive phenomenon is observed that the thicknesses of PdO electrode have a little impact on the sensor response. The sensing mechanism is discussed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Finding absolute selectivity towards CO remains a challenge for a PdO-SE operating at 550°C as it showed significant cross sensitivity towards hydrocarbons. 132 Nevertheless, mixed potential sensors are increasingly finding use in many applications. For example, the use of a mixed potential sensor with Pt/SnO 2 -SE in the operation of firewood combustion has helped to reduce the CO emissions by about 80% in comparison to hand-driven operation.…”
Section: Co Sensorsmentioning
confidence: 99%
“…Finding absolute selectivity towards CO remains a challenge for a PdO-SE operating at 550°C as it showed significant cross sensitivity towards hydrocarbons. 132 Nevertheless, mixed potential sensors are increasingly finding use in many applications. For example, the use of a mixed potential sensor with Pt/SnO 2 -SE in the operation of firewood combustion has helped to reduce the CO emissions by about 80% in comparison to hand-driven operation.…”
Section: Co Sensorsmentioning
confidence: 99%
“…They observed that 20-100 ppm CO could easily be detected at room temperature. (Zhu et al, 2015) realized that PdO powder & α-terpineol as working electrode and Pt as a counter electrode with yttria-stabilized zirconia could be a good combination for detection of CO. They observed that 20-200 ppm of CO could be detected in 118 seconds at 450 o C. In 2016, (Izu et al, 2016) used Pt for both working and counter electrodes with zirconia-doped ceria (Ce0.9Zr0.1O2) as the electrolyte and observed that 1000-5000 ppm of CO could be detected in 2-4 seconds at 400-500 o C. In the same year, (Shimizu et al, 2016) used Au/SnO2 as working electrode and Au as a counter electrode with anion-conducting polymer as the electrolyte for a CO sensor.…”
Section: Electrochemicalmentioning
confidence: 99%
“…3) Researchers have developed high-performance CO sensors based on different mechanisms, such as optical, resistive, electrochemical, potentiometric, and thermoelectric methods. [4][5][6][7][8][9] However, various problems posed by complicated and time-consuming processes, sensitivity degradation, and high costs make it difficult to apply the currently available gas sensors in industrial settings. Metal-oxide semiconductor (MOS) gas sensors based on microelectromechanical system technology are most widely used because of their simple process, small size, possibility of mass production, and easy integration into circuits and signal processing.…”
Section: Introductionmentioning
confidence: 99%